Evaluasi Perhitungan dan Pencatatan PPh Pasal 23 di Lembaga Nirlaba atau Organisasi Sosial yang Menggunakan Jasa Outsourcing Berkaitan dengan ISAK No 35 - Dini Ayu Pramitasari; Anisaul Hasanah; Mochammad Syafii; Bustanul Ulum; Mutiara Cahyani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to evaluate the calculation and recording of Income Tax (PPh) Article 23 in non-profit institutions or social organizations that use outsourcing services in relation to the implementation of ISAK No. 35. Using a descriptive qualitative research method, this study examines in depth the process of calculating Tax Article 23, the mechanisms of deduction, payment, and reporting, related accounting records, the level of compliance with ISAK No. 35 standards, as well as the problems and impacts of non-conformities that arise in practice. The results show that some non-profit institutions have calculated and deducted Tax Article 23 in accordance with the provisions, but there are still inaccuracies in the identification of tax objects, determination of rates, and administrative documentation. Accounting records show variations in compliance with ISAK No.35, especially related to transparency of disclosure and accountability of financial reports. In addition, there are obstacles such as limited understanding of human resources, lack of internal control systems, and minimal integration between the finance and tax departments. Inconsistencies in the management of Tax Article 23 have an impact on the potential for fiscal sanctions, decreased organizational credibility, and obstacles in presenting accurate financial reports. These findings are expected to contribute to improving tax and accounting governance in non-profit organizations so that they are more compliant with applicable tax regulations and financial reporting standards.